2012
DOI: 10.1152/japplphysiol.01079.2011
|View full text |Cite
|
Sign up to set email alerts
|

Corticomuscular coherence with and without additional task in the elderly

Abstract: Aging and dual-task paradigms often degrade fine motor performance, but the effects of aging on correlated neural activity between motor cortex and contracting muscle are unknown during dual tasks requiring fine motor performance. The purpose of this study was to compare corticomuscular coherence between young and elderly adults during the performance of a unilateral fine motor task and concurrent motor and cognitive tasks. Twenty-nine healthy young (18-38 yr) and elderly (61-75 yr) adults performed unilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 67 publications
5
46
1
Order By: Relevance
“…Although few studies have examined the role of an altered oscillatory drive in healthy older adults (Ͼ65 yr), this finding is consistent with the finding of increased interhemispheric EEG-EEG coherence (Maurits et al 2006;ten Caat et al 2008) and increased EEGand MEG-EMG coherence (Johnson and Shinohara 2012;Kamp et al 2011) in older adults during the performance of neurocognitive and motor tests. Increased oscillatory drive measured with motor unit recordings has also been linked with impaired performance during hand tasks in younger adults Kakuda et al 1999), and older adults frequently perform worse on motor tasks .…”
supporting
confidence: 79%
“…Although few studies have examined the role of an altered oscillatory drive in healthy older adults (Ͼ65 yr), this finding is consistent with the finding of increased interhemispheric EEG-EEG coherence (Maurits et al 2006;ten Caat et al 2008) and increased EEGand MEG-EMG coherence (Johnson and Shinohara 2012;Kamp et al 2011) in older adults during the performance of neurocognitive and motor tests. Increased oscillatory drive measured with motor unit recordings has also been linked with impaired performance during hand tasks in younger adults Kakuda et al 1999), and older adults frequently perform worse on motor tasks .…”
supporting
confidence: 79%
“…However, during sustained contractions of upper limb muscles, some studies reported age-related increase in the magnitude of coherence2728. Kamp et al 28.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no study has examined how aging affects corticomuscular coherence during cyclical, anti-phasic movements. Several studies have examined the effects of aging on corticomuscular coherence25262728, but these studies are limited to sustained contractions.…”
mentioning
confidence: 99%
“…Consequently, some studies show older adults have less ability to simultaneously perform a cognitive task and motor task as well as they can be performed individually (Voelcker-Rehage and Alberts, 2007; Fraser et al, 2010; Johnson and Shinohara, 2012). Changes in performance for older adults in dual-tasks appear to be especially sensitive to cognitive tasks that require executive function (Yogev-Seligmann et al, 2008).…”
Section: Discussionmentioning
confidence: 99%